Development of a highway safety manual - Hughes, Warren; Hughes, Warren Edward 1956-.; National Cooperative Highway Research Program; National Research Council (U.S.). Transportation Research Board (Washington, DC Transportation Research Board, 2004)
"This digest represents the results of NCHRP Project 17-18(04), 'Development of a highway safety manual.' This study developed an annotated outline, prototype chapter, and work plan for the first edition of the Highway safety manual. ..."--P. [1].
Caption title.
"March 2004."
Keywords: Roads -- United States -- Safety measures -- Handbooks, manuals, etc